Antigenemia temprana de Cryptococcus en pacientes asintomáticos VIH positivos en Barranquilla, Colombia - María C. Noguera-Angarita (Asociación Colombiana de Infectología, 2021)
Meningealcryptococcosis presents high levels of global mortality, especially in the HIV/AIDS population. The WHO recommends detecting the capsular antigen as an important strategy for early diagnosis and be able to minimize complications. Objective: Perform early cryptococcal antigenemia by immunochromatographic/lateral flow assay in asymptomatic HIV+ patients. Material and method: descriptive observational study; between July-2016 and May-2019, serum samples from 169 asymptomatic HIV+ patients with CD4 ≤120 cells/μL were processed by lateral flow assay in Barranquilla, Colombia. Given a positive result, prophylaxis with fluconazole was indicated; all cases were followed up. Results: antigenemia was positive in five (2.96%) patients; one died; four received prophylaxis, and the test turned negative in two. The patients with an initial negative result, did not developed symptoms compatible with this mycosis during the study period. Discussion: lateral flow assay for Cryptococcus is recommended for the early diagnosis of cryptococcosis in the HIV/AIDS population. Conclusion: early detection of circulating Cryptococcus antigen by lateral flow assay in HIV+ patients allowed the establishment of timely prophylaxis, follow-up, and control to reduce mortality associated with meningeal cryptococcosis.